A revision of the generic status of Periclimenes jackhintoni Bruce, 2006, with a new key to the genus Laomenes Clark (Crustacea: Decapoda: Palaemonidae) - Bruce, A. J. (Zootaxa, 2007)
The genus Laomenes was designated by A.H. Clark (1919), as a replacement name for the preoccupied name Corniger Borradaile 1915. Until recently subsequent authors considered it to be a synonym of Periclimenes Costa 1844. Only three species were referred to this genus, as P. amboinensis (De Man, 1888), P. ceratophthalmus Borradaile, 1915, and P. cornutus Borradaile, 1915. The genus Laomenes Clark has now been resurrected by Okuno and Fujita (January 2007), with the additional inclusion of a further species, Parapontonia nudirostris Bruce, 1968, the genus Parapontonia Bruce, 1968, being regarded as a junior synonym of Laomenes Clark.